2012
DOI: 10.1111/j.1365-3016.2012.01314.x
|View full text |Cite
|
Sign up to set email alerts
|

The SELMA Study: A Birth Cohort Study in Sweden Following More Than 2000 Mother–Child Pairs

Abstract: These findings indicate that the participating families do not fully represent the study population and thus, the exposure in this population. However, there is no obvious reason that this selection bias will have an impact on identification of environmental risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 36 publications
2
69
0
Order By: Relevance
“…The participation rate of 37% is consistent with participation rates of several large pregnancy cohorts. 24 As in other pregnancy cohort studies, 15 Those who responded to self-administered questionnaires and who participated in postnatal follow-up visits tended to be older, of lower parity, had higher household incomes and education levels, and were less likely to smoke. Combined with the relatively high socio-economic status of the study population, these differential response rates are likely to limit generalizability of results from this cohort, particularly in psychosocial and developmental domains.…”
Section: Commentmentioning
confidence: 80%
“…The participation rate of 37% is consistent with participation rates of several large pregnancy cohorts. 24 As in other pregnancy cohort studies, 15 Those who responded to self-administered questionnaires and who participated in postnatal follow-up visits tended to be older, of lower parity, had higher household incomes and education levels, and were less likely to smoke. Combined with the relatively high socio-economic status of the study population, these differential response rates are likely to limit generalizability of results from this cohort, particularly in psychosocial and developmental domains.…”
Section: Commentmentioning
confidence: 80%
“…Snart Gravid participants were more likely to be nonsmokers and nulliparous and less likely to be <25 or more than 34 years old. Previous studies of birth cohorts recruited using traditional methods also found that their study participants were more likely to be nulliparous, 15,16,33 nonsmoking, 13,16,33 and between 25 and 34 years old 15,16 than their source populations identified via registries. Similar to these studies, we found that most exposure–outcome associations were comparable for women who participated in our prospective cohort study and all Danish women in the Danish Medical Birth Registry, even though Snart Gravid recruited participants via the internet and the study population was confined to pregnancy planners.…”
Section: Discussionmentioning
confidence: 91%
“…The authors predicted that if psychiatric symptoms positively correlate with HG, then psychiatric symptoms would correlate positively with recurrence risk. As the study was based on data from an online survey, the participating women were not randomly selected among women with HG and may therefore have had a different risk profile from the women who did not participate (Bornehag et al 2012). Additionally, only women who had had at least two pregnancies lasting beyond the second trimester were included, which may introduce recall bias, e.g.…”
Section: Discussionmentioning
confidence: 99%